Reforming transport pricing in the European Union a modelling approach - Borger, Bruno de.; Proost, Stef.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2001)
This timely book deals with the problem of pricing passenger and freight transportation within Europe. The contributors argue that current legislation affecting pricing and regulation is increasingly less successful in dealing with market failures and externalities such as congestion, air pollution, noise and accidents. Technological progress and greater European co-operation has brought increased scope for the reform of transport policies.
pt. 1. Principles -- pt. 2. Modelling -- pt. 3. External and internal costs -- pt. 4. Case studies.
Includes bibliographical references and index.
Keywords: Transportation -- Prices -- European Union countries -- Econometric models; Electronic books